Improvements in survival for patients with stage IV adenocarcinoma in the lung, diagnosed between 2010 – 2020 - A population-based registry study from Norway - Børø, Siri; Thoresen, Steinar; Helland, Åslaug (Frontiers in Oncology, 2022)
Objectives We investigated how the prognosis for Norwegian patients with stage IV, adenocarcinoma (NSCLC) has developed during the last decade, to observe if increased survival coincides with the introduction of immunotherapy at a population level. Materials and methods Incidence data from the Cancer Registry of Norway are virtually complete and includes information about histological subtypes and biomarkers. The data was used to analyze median and relative survival for females and males diagnosed with stage IV NSCLC, divided by histological subgroups and age-groups. Results During 2010 – 2020, 14472 patients were diagnosed with lung cancer in stage IV, in Norway. Among them 6351 patients (43 %) were classified with adenocarcinoma. The median survival has increased for both sexes, but the largest increase in seen in females. From 2010 to 2020, median survival for females in the 0-69 group increased from 6.7 months to 12 months and from 3.7 months to 10 months for the 70+ age group. For the equivalent male age groups, we see an increase from 6.1 months to 7.7 months for the 0-69 group, and an increase from 3.8 months to 4.5 months for the 70+ group. When excluding patients with EGFR/ALK mutations from the survival analysis, the groups continue to display an increased survival from 2010 to 2020, although modest in the male 70+ group. The 1-year relative survival (RS) has increased for both sexes, from 32.4 % to 51.2 in females and 25.4 % to 44.5% in males. When EGFR/ALK positive patients were excluded from the analysis 1-year RS in females rose from 32.4 % to 47.4 % and for males from 25.4 % to 41.8 %. Conclusion A real-world patient population of stage IV, NSCLC adenocarcinoma have had a clinically meaningful increase in both median and relative survival from 2010 – 2020. The steepest survival increase has taken place after 2016, the time point where immunotherapy was implemented as a treatment option for the stage IV, adenocarcinoma population not harboring targetable mutations (EGFR/ALK).